Outcomes of migration as adaptation: a conceptual framework for migration governance - Kali Abel; Brian Katz; Stefan Rose; David Wrathall (Journal of Integrative Environmental Sciences, 2023)
Climate change – along with conflict, violence, and climate-related disasters – has the potential to accelerate many forms of human migration and mobility, and yet almost all of the key migration outcomes of interest (the decision to migrate, the timing of migration, the preferred destinations, the condition of migrants, outcomes of migration, etc.) are determined by governance decisions. While it is well documented that migration as adaptation can increase the adaptive capacity for both migrants and destination communities, policy decisions can lead to both barriers to or opportunities for desired outcomes within a governance landscape. Though the decision to leave a place of origin is frequently studied, less attention has been given to the outcomes for migrants within a chosen destination, and the often-opaque elements that contribute to destinations being preferred or avoided. Under current climate change scenarios, the demand for migration as adaptation is increasing and the conceptual framework presented here is guided by the need to understand how intended and unintended consequences of host-centred, migrant-centred, or mutual migration governance affect migrants in a destination regardless of the driver. The conceptual framework we present, comprised of four potential governance “quadrants”, is used for defining variability within a polycentric governance landscape in order to understand the formal and informal governance elements that produce outcomes for both migrant and host communities. We then apply the framework, making contact with three case studies within Oregon’s diverse governance landscape, and explore the degree to which variability in a governance landscape creates destinations that are favourable or unfavourable to migrants, elucidating the informal and formal governance elements that enable or limit preferred migration outcomes. In a future in which migration is likely to be influenced by a changing climate, a conceptual framework, such as this may aid in elucidating the structural conditions that shape livelihood outcomes for migrants and host communities.